2021
DOI: 10.1371/journal.ppat.1010151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RNA synthesis initiation properties of non-segmented negative strand RNA virus polymerases

Abstract: It is generally thought that the promoters of non-segmented, negative strand RNA viruses (nsNSVs) direct the polymerase to initiate RNA synthesis exclusively opposite the 3´ terminal nucleotide of the genome RNA by a de novo (primer independent) initiation mechanism. However, recent studies have revealed that there is diversity between different nsNSVs with pneumovirus promoters directing the polymerase to initiate at positions 1 and 3 of the genome, and ebolavirus polymerases being able to initiate at positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In a previous study, we showed that although the PIV-3 polymerase initiates only at position 1 of its own promoter, it initiates at positions 1 and 3 of the RSV promoter (like the RSV polymerase). Likewise, we showed that although MARV polymerase only initiates at position 1 of its own promoter, it too can initiate efficiently at an internal site at position 2 of the Ebola virus promoter (39). These findings indicate that while nsNSVs have differences in their promoters and sites of initiation, their polymerases have similar properties.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In a previous study, we showed that although the PIV-3 polymerase initiates only at position 1 of its own promoter, it initiates at positions 1 and 3 of the RSV promoter (like the RSV polymerase). Likewise, we showed that although MARV polymerase only initiates at position 1 of its own promoter, it too can initiate efficiently at an internal site at position 2 of the Ebola virus promoter (39). These findings indicate that while nsNSVs have differences in their promoters and sites of initiation, their polymerases have similar properties.…”
Section: Discussionmentioning
confidence: 79%
“…As shown in the alignment presented in Fig 1B, the filovirus MARV L protein does not have an aromatic residue corresponding to the rabies virus L Trp1180, but it does have a proline residue (Pro1217) that aligns with RSV L Pro1261 and an aromatic tyrosine residue (Y1218) that aligns with RSV L Trp1262. Since we have recently established an in vitro RNA synthesis initiation assay for the MARV polymerase (39), we used this approach to test the effect of substituting MARV L Pro1217 and Tyr1218 with alanine. The mutant L-VP35 complexes were isolated and tested in an on-bead RNA synthesis assay using an RNA template consisting of nucleotides 1-30 of the MARV le promoter sequence (Fig 7A and 7B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5'-pppA is generated by viral RdRp that recognizes the opposite U as the template. As seen in several segmented and non-segmented RNA viral polymerases (18)(19)(20), bunyaviral RdRp synthesizes RNA from an internal nt, and not from the terminus of the template. In LACV, RNA synthesis is initiated with A using the U at the +4 position of the antigenome 10 (3'-UCAUCA) as the template during genome replication (9).…”
Section: Discussionmentioning
confidence: 99%